2003
DOI: 10.1002/oa.666
|View full text |Cite
|
Sign up to set email alerts
|

The application of ancient DNA analysis to identify neolithic caprinae: a case study from the site of Hatoula, Israel

Abstract: The evidence for wild sheep (Ovis orientalis) in archaeological sites from the southern Levant is examined through the application of ancient DNA analysis to specimens from the Pre-Pottery Neolithic A (8300-7500 uncal. BC) site of Hatoula, Israel. The results indicate that at least one of the bones from this site, previously identified as sheep, is in fact goat. To date this is the earliest faunal sample to have yielded DNA in the region. This study highlights the problems in applying morphological criteria to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…[ 49 , 51 52 ]. All five haplogroups have also been detected in ancient populations [ 10 , 16 , 43 – 45 , 53 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…[ 49 , 51 52 ]. All five haplogroups have also been detected in ancient populations [ 10 , 16 , 43 – 45 , 53 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Larger average body size at Abu Gosh may relate to the inclusion of C . ibex measurements in the LSI data [95], but the LSI distribution is positively skewed, and likely indicates a slight female bias. The Bos LSI distribution from KHH combines measurements from all PPNB phases to maximize sample size and includes many measurable bones that could be dated only to the PPNB.…”
Section: Resultsmentioning
confidence: 99%
“…Among other things, studies incorporating aDNA have shown that ancient sheep essentially belong to the same haplogroups as identified for modern breeds (Kahila Bar‐Gal et al . ; Cai et al . , ; Olivieri et al .…”
Section: Introductionmentioning
confidence: 99%